Discrepancy between left ventricular hypertrophy by echocardiography and electrocardiographic hypertrophy: clinical characteristics and outcomes - Takao Kato; Moriaki Inoko; Yuta Seko; Yuhei Yamaji; Eisaku Nakane; Tetsuya Haruna; Yoshisumi Haruna (Open Heart)
Background The clinical significance of the discrepancy between left ventricular hypertrophy (LVH) by echocardiography and ECG remains to be elucidated.Methods After excluding patients who presented with pacemaker placement, QRS duration ≥120 ms and cardiomyopathy and moderate to severe valvular disease, we retrospectively analysed 3212 patients who had undergone both scheduled transthoracic echocardiography (echo) and ECG in a hospital-based population. Cornell product >2440 mm · ms was defined as ECG-based LVH; left ventricular mass index >115 g/m2 for men and >95 g/m2 for women was defined as echo-based LVH. The study population was categorised into four groups: patients with both ECG-based and echo-based LVH (N=131, 4.1%), those with only echo-based LVH (N=156, 4.9%), those with only ECG-based LVH (N=409, 12.7%) and those with no LVH (N=2516, 78.3%).Results The cumulative 3-year incidences of a composite of all-cause death and major adverse cardiovascular events were 32.0%, 33.8%, 19.2% and 15.7%, respectively. After adjusting for confounders, the HRs relative to that in no LVH were 1.63 (95% CI 1.16 to 2.28), 1.68 (95% CI 1.23 to 2.30) and 1.09 (95% CI 0.85 to 1.41) in patients with both ECG-based and echo-based LVH, those with only echo-based LVH, and those with only ECG-based LVH, respectively.Conclusions Echo-based LVH without ECG-based LVH was associated with a significant risk of adverse clinical events, and the risk was comparable to that in patients with both echo-based and ECG-based LVH.